2010
DOI: 10.1007/s00244-010-9573-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organism Density on Bioaccumulation of Contaminants from Sediment in Three Aquatic Test Species: A Case for Standardizing to Sediment Organic Carbon

Abstract: Laboratory methods for measuring bioaccumulation of organic contaminants from sediment into aquatic organisms continue to improve, but some aspects are still in need of standardization. From a review of published methods, we noted that the loading density of organisms was determined inconsistently and was primarily based on either sediment volume or total organic carbon (TOC). The rationale mainly expressed for standardizing to TOC was to minimize the depletion of sediment contaminants. However, even when dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
2
16
1
Order By: Relevance
“…1 and Supplemental Data: Table S4). The observation of increasing loadings of organism causing decreasing growth is contrary to the studies of Van Geest et al (2011) and Kukkonen and Landrum (1994) in which there was no relationship between growth and loading of the L. variegatus. This study used a larger set of sediments and a wider range of loading of the organisms.…”
Section: Hr 93contrasting
confidence: 82%
See 2 more Smart Citations
“…1 and Supplemental Data: Table S4). The observation of increasing loadings of organism causing decreasing growth is contrary to the studies of Van Geest et al (2011) and Kukkonen and Landrum (1994) in which there was no relationship between growth and loading of the L. variegatus. This study used a larger set of sediments and a wider range of loading of the organisms.…”
Section: Hr 93contrasting
confidence: 82%
“…In a review of sediment-testing methods (Van Geest et al 2010), other ratios of TOC/Lv have been used with the sediment-bioaccumulation test, and the review suggested that an optimal organisms density might not exist for all sediments. In follow-up work by Van Geest et al (2011), PCB residues from sediment-bioaccumulation tests performed at ratios of 50:1 and 27:1 were not significantly different. Ontario Ministry of the Environment testing protocols have adopted the 27:1 ratio (Van Geest and Watson-Lueng 2013) and all tests are performed using this ratio in their sediment-bioaccumulation tests with L. variegatus.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The standard bioaccumulation testing protocol (USEPA 2000) specifies that the ratio of total OC in the sediment to organism dry weight should be no less than 50:1 in this test; some of the tested sediments did not meet this requirement (Tables S3 and S6). Bioaccumulation testing with L. variegatus at a ratio of 27:1 has been shown to provide the same results as the 50:1 ratio (Van Geest et al 2011). …”
Section: Sediment Bioaccumulation Testsmentioning
confidence: 78%
“…Tests were conducted at 23 AE 2 8C, under a 16:8 h light:dark photoperiod with an intensity of 500 to 1,000 lux. Based on previous research evaluating the effect of loading density on organism survival, growth, and bioaccumulation, a ratio of approximately 27:1 TOC to organism dry weight was selected as a standard loading density of organisms for the bioaccumulation method [15].…”
Section: Bioaccumulation Test Methodsmentioning
confidence: 99%